Einseitig erklärter Eigentumsvorbehalt und Käuferinsolvenz Vorleistungspflicht, Synallagmaschutz und Gläubigerprivilegierung in der Insolvenz - Riss, Olaf (2023)
The reservation of title is a popular credit security instrument in numerous legal systems. If the sales contract lacks an effective reservation of title clause, the crediting seller sometimes tries to remedy this deficiency retrospectively: He declares at the time of handover that ownership does not pass to the buyer - contrary to the legal rule (§ 1063 ABGB) - until the purchase price has been paid in full. If the buyer does not agree to this request for a subsequent amendment of the contract, this is referred to as a unilaterally declared retention of title.